The cross-transition of deformation twinning in magnesium. (1st January 2022) - Yang, Nan; Liu, Bo-Yu; Liu, Fei; Shan, Zhi-Wei
Abstract: Deformation twinning operates via twinning dislocations gliding on a specific twinning plane and along a specific twinning direction. As a consequence, a twin variant is supposed to retain its identity and unable to transform into other variants. However, we demonstrated that for the 10 1 ¯ 2 deformation twinning in magnesium, one twin variant can transform towards its conjugated variant in response to the external applied loading via the participation of prismatic-basal interface migration. We term such transformation as cross-transition of deformation twinning, which is expected to broaden the understanding of twinning mechanism. Graphical abstract: Image, graphical abstract